Application of Input Management and Integrated Pest Management on Paddy Production: Case Study in Kampar Subdistrict, Kampar District, Riau Province - Amalia; Syaukat, Yusman; Hakim, Dedi Budiman; Dadang (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The attack levels of plant pest organisms (PPO) highly influence the productivity of paddy rice farming. With the increasing human awareness of the dangers of using pesticides, especially for the environment and human health, PPO control prioritizes preventive control by applying the principles of integrative pest management (IPM), which prioritizes the application of healthy crop cultivation, routine observation, utilization of natural enemies and farmers as IPM experts. The use of inputs by farmers in production activities can affect the resulting production. This study aimed to estimate the effect of input management, IPM, and non-IPM on paddy rice production. The analysis used in this study was the Cobb-Douglas production function with the multiple linear regression method. Partially, each variable of land area, seeds, inorganic fertilizers, and dummy variables of IPM or non-IPM farmers significantly affected paddy rice production in Kampar Subdistrict. Variables of organic fertilizers, natural pesticides interacted with frequency, chemical pesticides interacted with frequency, and labor partially had no significant effect on lowland paddy rice production in Kampar Subdistrict. It is necessary to re-enact counseling on IPM in Kampar Subdistrict, Kampar District, to apply IPM principles that prioritize preventive PPO control to avoid the dangers of using pesticides for the environment and human welfare. Keywords: Cobb-Douglas, plant pest organisms, integrative pest management, non-IPM, rice paddy production